Technical and Economic Evaluation of a Small-Scale Wind Power System Located in Berlin, Colombia. - Pinto Calderón, María de los Ángeles; Moreno Calderón, Jennyffer Katerine; Muñoz Maldonado, Yecid Alfonso; Ospino Castro, Adalberto (TECCIENCIA, 2018)
This work evaluates the possibility of increasing the national and regional competitiveness from the local generation of energy in Berlin – Santander, based on a technical and economic feasibility assessment of a small-scale wind energy generation system. Despite the important growth wind energy in Colombia has acquired over the last years, there is still a very limited number of investigations and projects. For the Andean region of Colombia there is a considerable lack of academic or industrial projects that address this topic. Hence, the importance of the study lies down in the potential explored for an environment that had not yet been addressed and may become determinant for the technological and academic advancement in the wind energy knowledge for the country. The study is conducted from a database provided by the Institute of Hydrology, Meteorology and Environmental Studies (IDEAM) at a meteorological station located in Berlin-Santander. The available wind potential is calculated for the climatic conditions of 2015. Three different Wind Energy Conversion Systems (WECS), 1 kW, 3 kW and 900 kW, are technically compared to determine the best option for the given conditions. Finally, a brief economic evaluation is carried out to determine the economic viability of the project and lay the groundwork for further investigations.